Age Structure, Growth, and Mortality of Blue Swimming Crab (Portunus pelagicus Linnaeus,1758) in Banten Bay Waters - Aulia, Imadiah; Khalifa, Muta Ali; Rahmawati, Ani; Syauqi, Muhammad; Wahyuningsih, Mila; Raimahua, Syifa Jihan; Akmalia, Wilda (Jurnal Biodjati, 2023)
Blue swimming crab (BSC) (Portunus pelagicus) is the main fisheries commodity in Banten Bay, with the highest catch of catch occurring in the west monsoon. Increased fishing efforts have reduced the catch, as indicated by a decrease in the average size of carapace width. Overfishing might influence the life cycle and population structure of the BSC. This research aims to analyze the growth and mortality of the Blue Swimming Crab in Banten Bay, especially in the west monsoon. Blue swimming crab samples were obtained from the catch of fish trap and gillnet fishermen with landing sites around the Karangantu Archipelago Fishing Port. Growth, age, and mortality were predicted based on the measurement of total carapace width and body weight. Data were analyzed using Fisat II and Microsoft Excel. The frequency distribution of carapace showed one mode class which normally was distributed consisting of only one age structure group (cohort). The relationship between carapace width and weight of males or females resulted in a slope value (b>3) and was positive allometric, indicating that both sexes had a faster weight gain than the increase in carapace width. Growth parameters resulted asymptotic length (Lâˆž); male 176.75 mm and female 176.46 mm. The growth was relatively fast, with a growth coefficient value of more than one. The mortality showed that the fishing mortality value (F);in males was 3.47 /year and in females 2.69/year was greater than the natural mortality value (M); males 1.25/year and females 1.22/year. Blue Swimming Crabs in Banten Bay had overfished as shown by the high fishing mortality value and there were still many BSC that were caught below the legal size allowed. Thus, catches should be controlled to keep the population and for sustainable fisheries.